Area Deprivation and Pediatric Cancer Mortality: An Analysis of 2000 to 2020 State Cancer Registry Data - Hymel, Emma; Peters, Edward S; Ratnapradipa, Kendra L; Zheng, Cheng; Allison, Jenna; Hsieh, Mei-Chin; Nash, Sarah H; Watanabe-Galloway, Shinobu (Cancer epidemiology, biomarkers & prevention, 2025)
Compared with adult cancers, less research has been conducted on health disparities in pediatric cancer outcomes. The effect of neighborhood deprivation, as measured by the Area Deprivation Index (ADI), on pediatric cancer survival is not well understood, especially among diverse populations. We conducted a population-based longitudinal study using data from the Iowa Cancer Registry and Louisiana Tumor Registry. The study included children ages 0 to 19 years diagnosed with cancer in Iowa and Louisiana from 2000 to 2020. The primary exposure was ADI, and the primary outcome was cancer-specific mortality. Cox regression models with shared frailty to account for the geographic clustering of individuals were used to compute the association between ADI and mortality. A total of 6,982 children were included between the two states: 2,939 in Iowa and 4,043 in Louisiana. In the adjusted analysis, higher deprivation was positively associated with poorer pediatric cancer survival. Compared with children in the least deprived neighborhoods, those in the most deprived neighborhoods had a 50% higher risk of cancer death [95% confidence interval (CI), 1.18-1.89] and a 3.15 times greater risk of early cancer death (95% CI, 1.39-7.16). Among children with extracranial solid tumors, those in the most deprived neighborhoods had a 54% higher risk of cancer death (95% CI, 1.04-2.27) compared with those in the least deprived neighborhoods. Higher ADI is associated with higher pediatric cancer mortality, highlighting the importance of social drivers of health on pediatric cancer outcomes. Neighborhood-level interventions will likely be needed to improve pediatric cancer outcomes.